Conflict of interest policies and disclosure requirements among European Society of Cardiology national cardiovascular journals - Fernando Alfonso; Adam Timmis; Fausto J. Pinto; Giuseppe Ambrosio; Hugo Ector; Piotr Kulakowski; Panos Vardas (Кардиоваскулярная терапия и профилактика)
.